PENGARUH PENYAKIT DIABETES MELITUS DAN HIPERTENSI TERHADAP VISUS PASIEN USIA LANJUT PASCA OPERASI KATARAK DENGAN METODE SICS DI RS MATA NTB TAHUN 2024 - Widia Rahmayana (Jurnal Medika Hutama, 2025)
Background: Visual acuity (visus) refers to the eye's ability to perceive fine details at a specific distance. According to WHO (2021), visual impairments include blindness and conditions that cannot be corrected with glasses or contact lenses. These impairments may result from cataracts, glaucoma, macular degeneration, or diabetic retinopathy. Research indicates that visual impairments are more prevalent among older adults and individuals with comorbidities such as diabetes and hypertension. Cataracts, a condition where the lens of the eye becomes cloudy and causes blurred vision, are commonly found in older adults. WHO identifies cataracts as the second leading cause of global visual impairment (33%) after uncorrected refractive errors (42%). Uncontrolled diabetes mellitus (DM) can lead to severe complications, including damage to the eyes, kidneys, nerves, and heart. In patients with hypertension, increased oxidative stress occurs. Methods: This study is an analytical observational study with a cross-sectional approach. The population consisted of all elderly cataract patients who underwent surgery at the NTB Eye Hospital in 2024 and had comorbidities such as hypertension and diabetes mellitus. Results: The statistical chi-square test showed no significant effect of diabetes mellitus on the visual acuity of elderly patients after cataract surgery, with a p-value of 0.143 (P > 0.05). Similarly, there was no significant effect of hypertension on visual acuity in elderly patients after cataract surgery, with a p-value of 0.143 (P > 0.05). Conclusion: There is no significant effect of diabetes mellitus or hypertension on the visual acuity of elderly patients after cataract surgery using the SICS method at the NTB Eye Hospital in 2024.